2021
DOI: 10.1002/jdd.12606
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of blended learning for teaching dental anatomy to dentistry students

Abstract: Objectives Blended learning (BL) combines conventional face to face (F2F) sessions with online educational resources. This method includes the advantages of online course delivery without the omission of conventional F2F interaction. The purpose of the present study was to evaluate students' satisfaction and educational outcomes in a BL course compared to traditionally administered dental anatomy course. Methods A prospective non‐randomized study was conducted to compare the outcomes and perception of BL for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
2
18
0
2
Order By: Relevance
“…al concluded that a blended learning platform in teaching dental anatomy was associated with improved students' satisfaction and learner performance compared to a conventionally administered dental course. 12 Yakin and Linden reported that first-and third-year dental students perceived online materials improved their knowledge of histology topics. 13 This study adds to the growing body of evidence that supports that a hybrid mode of delivering dental education can be effective, even for a topic that is hands-on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al concluded that a blended learning platform in teaching dental anatomy was associated with improved students' satisfaction and learner performance compared to a conventionally administered dental course. 12 Yakin and Linden reported that first-and third-year dental students perceived online materials improved their knowledge of histology topics. 13 This study adds to the growing body of evidence that supports that a hybrid mode of delivering dental education can be effective, even for a topic that is hands-on.…”
Section: Discussionmentioning
confidence: 99%
“…Ullah et. al concluded that a blended learning platform in teaching dental anatomy was associated with improved students’ satisfaction and learner performance compared to a conventionally administered dental course 12 . Yakin and Linden reported that first‐ and third‐year dental students perceived online materials improved their knowledge of histology topics 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Además, Hyflex permite poder trabajar de forma simultánea, tanto a los alumnos remotos como a los presenciales, manteniendo un alto grado de interacción e intercambio personal, permitiendo beneficiarse de las experiencias positivas y negativas del resto (Weissmann et al, 2021). Para los estudiantes es fundamental tener una interacción fluida con sus pares y docentes, lo cual ha sido descrito en el paradigma de aprendizaje social (Ullah et al, 2021), ya que permite favorecer el compromiso afectivo y mejorar la eficiencia del trabajo, influyendo positivamente en el proceso de aprendizaje.…”
Section: Discussionunclassified
“…Esto determina que los alumnos y docentes perciban que a mayor presencialidad es mayor la calidad de aprendizaje, mayor rendimiento, mayor vínculo con los docentes, debido a que no existe problemas en la recepción de la información. Esto es lo que sucede en los cursos online, donde hay disminución del compromiso del estudiante remoto y su motivación (Ullah et al, 2021), ya que se sienten aislados (Nweke et al, 2022), pasando a ser fundamental la autorregulación de individuo (Kohne & Moorhouse, 2021). Lo anterior crea un desafío para las universidades, ya que el modelo Hyflex requiere de una apropiada infraestructura, soporte audiovisual, y capacitaciones técnicas y pedagógicas para los docentes previo a su aplicación (Detyna et al, 2022).…”
Section: Discussionunclassified
“…Various models of blended learning are used in education (18), including Rotation (Station Rotation, Lab Rotation, Individual Rotation and Flipped Classroom), Self-Blend, Flex, and Enriched Virtual model (19). Numerous studies have con rmed the effectiveness of these methods (20)(21)(22)(23)(24). One of the most widely used models of blended learning is the Flipped Classroom.…”
Section: Introductionmentioning
confidence: 99%